2015
DOI: 10.1016/j.envres.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seafood mediated PCB exposure on desaturase activity and PUFA profile in Faroese septuagenarians

Abstract: Polychlorinated biphenyl (PCB) exposure may affect serum concentrations of polyunsaturated fatty acids (PUFAs) by inhibiting desaturases Δ5 and Δ6 that drive their synthesis from precursor fatty acids. Such changes in the composition of fatty acids may affect cardiovascular disease risk, which is thought to increase at elevated PCB exposures. This population-based cross-sectional study examined 712 Faroese men and women aged 70–74 years. The serum phospholipid fraction of fasting blood samples was used to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Lastly, the multiple linear regression models showed that PCB 180 + 193 serum levels are predicted by maternal plasma polyunsaturated fatty acid levels. PCBs have previously been associated with polyunsaturated fatty acids in human serum due to the high prevalence of both PCBs and PUFAs in fish and fish oil ( Ashley et al, 2013 ; Bourdon et al, 2010 ; Dellinger et al, 2018 ; Ge et al, 2019 ; Tøttenborg et al, 2015 ). However, we did not include dietary information in this study, so cannot validate a hypothesis for the association between PCB 180 + 193 and dietary polyunsaturated fatty acid intake.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, the multiple linear regression models showed that PCB 180 + 193 serum levels are predicted by maternal plasma polyunsaturated fatty acid levels. PCBs have previously been associated with polyunsaturated fatty acids in human serum due to the high prevalence of both PCBs and PUFAs in fish and fish oil ( Ashley et al, 2013 ; Bourdon et al, 2010 ; Dellinger et al, 2018 ; Ge et al, 2019 ; Tøttenborg et al, 2015 ). However, we did not include dietary information in this study, so cannot validate a hypothesis for the association between PCB 180 + 193 and dietary polyunsaturated fatty acid intake.…”
Section: Resultsmentioning
confidence: 99%
“…38 These findings were supported in a birth cohort study conducted in the Faroe Islands where the cord serum levels of PCBs were inversely associated with the concentrations of AA 39 and in a cohort of elderly people where the PCB levels in serum were also inversely related to the estimated Δ6 desaturase activity and larger concentrations of fatty acids precursors. 40 Uptake, storage and transport of dietary vitamin A and its related congeners (ie, β-carotene and retinyl esters) are regulated by the retinoid system, target of multiple endocrine-disrupting chemicals including dioxins, PCBs or pesticides. Given the fundamental role of retinoids in multiple physiological processes, the perturbation of vitamin A metabolism has been suggested as a putative mechanism triggering or mediating POPs-induced adverse health effects related to the immune system function, reproduction or development.…”
Section: Toxicodynamic Interactionsmentioning
confidence: 99%